APLIKASI PERANCANGAN WEBSITE PERSEKUTUAN OIKUMENE STMIK JAKARTA STI&K MENGGUNAKAN MICROSOFT FRONTPAGE 2003 - Jonathan Pratama; Marzuki, SKom.MMSI Marzuki, SKom.MMSI (Jurnal Sistem Informasi, 2006)
Media information is a means to convey a message or information that we received, bothorally and in writing, and various kinds such as newspapers, television, radio andcomputers.Internet is one medium of information very quickly. The required information must beinformation very quickly, accurately, and can be held responsible for authenticity.Ecumenical Fellowship (PO) is one of the central information and aspirations of thestudent / First Christian STMIK STI & K. Jakarta For the implementation of applicationsoftware can use Microsoft FrontPage 2003 so that the contents of the site moreinteresting.With this website students are expected to PO / I STMIK Jakarta Christian STI & K canobtain information and to channel their aspirations.